Study on Application of Double-pipe Condenser for Auto-cascade Refrigeration - Rui Shengjun; Zhang Hua; Wang Hongnian; Li Juanjuan (Zhileng xuebao)
Auto-cascade refrigeration system is widely used to obtain low temperature environment between -40 ℃ ~ -150 ℃. Double-pipe condenser is commonly regarded for condensing equipment in auto-cascade refrigeration system, its characteristics and structure affects refrigeration equipment system deeply. An auto-cascade refrigeration system with double-pipe condenser as the research object, the condensing process characteristics and structure dimension were studied. At the condensing pressure of 2.0 MPa, the condensing load was 1610W when the mass fraction ratio of R600a and R23 was 7:3. The structure size of double-pipe condenser was 4.842m based on the heat transfer coefficient of mixed refrigerant and cooling water. At the end of the paper the suction temperature, exhaust temperature, evaporation temperature in different condensing water flow, and inlet and outlet temperature of cooling water were analyzed.